Response of Potato (Solanum tuberosum L.) to NPS Fertilizer Rates and Inter-Row Spacing in Kechi District, South Western Ethiopia - Lakew Getaneh; Fanuel Laekemariam (Applied and Environmental Soil Science)
Fertilizer requirement and spacing vary across locations due to differences in soil types, nutrient and moisture availability, economic factors, and other environmental conditions. Therefore, a field experiment was carried out to investigate the effect of different rates of NPS fertilizers and inter-row spacing on growth, yield, yield components, and economic performance of potato in Kechi research farm, Dawro zone of south-western Ethiopia. The experiment was arranged in factorial combination of six NPS (19N–38P2O5–7S) fertilizer rates (0 kg/ha, 50 kg/ha, 100 kg/ha, 150 kg/ha, 200 kg/ha, and 250 kg/ha) and five inter-row spacings (45, 55, 65, 75, and 85 cm) which were laid out in RCBD with three replications using the Gudene variety. Growth, yield component, and yield data were collected and analyzed. In addition, a partial budget analysis was performed. The results showed that the main effect of NPS fertilizer and inter-row spacing had significantly (P<0.05) affected plant height, tuber number, tuber yield, and tuber size and average tuber weight. Maximum marketable tuber number per plant (11.627), total tuber number per plant (13.020), average tuber weight per plant (83.493 g), the proportion of large-sized tuber number per plant (41.893%), marketable tuber yield (48.056 t/ha), and total tuber yield (51.145 t/ha) were obtained from 200 kg/ha of NPS fertilizer which was statistically at par with 150 kg/ha and 250 kg/ha NPS, while the lowest result for those parameters was recorded from unfertilized plots. Results regarding inter-row spacing revealed that the highest marketable tuber number per plant (11.744), total tuber number per plant (13.144), and average tuber weight per plant (85.559 g) were recorded at 75 cm, while the lowest result for these parameters was recorded at 45 cm. Moreover, the highest marketable tuber yield (45.084 t/ha) and total tuber yield (48.462 t/ha) were obtained from the inter-row spacing of 65 cm which was statistically at par with 55 cm inter-row spacing, while the lowest result for these parameters was recorded at 85 cm. The partial budget analysis further revealed that 200 kg/ha NPS fertilizer gave the maximum net benefit. However, 150 kg/ha NPS resulted in the highest marginal rate of return (4303.91%). Thus, 150 kg/ha NPS fertilizer and inter-row spacing of 55 cm or 65 cm are suggested for attaining higher potato yield.